The Role of Post-Story Activities in Developing Critical Thinking Skills in Early Childhood: An Educational Theoretical Perspective (The International Journal of Educational Sciences and Arts, 2025)
This theoretical study aims to highlight the effectiveness of post‐story activities as a narrative‐based educational strategy for developing critical thinking skills in early childhood. Adopting a constructivist framework grounded in Bruner’s theory—which emphasizes teaching skills according to the learner’s cognitive readiness rather than chronological age, the study proceeds with a critical analysis of contemporary neuroscience research that supports the deconstruction and simplification of complex skills for young children and underscores the role of storytelling strategies and related activities in cultivating these skills. It then reviews empirical studies exploring the relationship between narrative and critical thinking. The research seeks to identify mechanisms for engaging with the story text after its presentations such as interactive discussions, kinesthetic games, and brainstorming sessions—and to design applied activities that foster inquiry, analysis, and evaluation. Additionally, it examines factors influencing the effectiveness of these activities, including the teacher’s role, the classroom environment, and appropriate assessment methods. In conclusion, the study offers practical recommendations for integrating post‐story activities into curricula and proposes teacher‐training programs to enable educators to facilitate analytical discussions effectively, thereby enhancing children’s critical thinking and problem‐solving abilities.
Keywords: Critical Thinking; Post-Story Activities; Early Childhood; Educational Psychology; Narrative Learning